Soybean leaf age and plant stage influence expression of resistance to velvetbean caterpillar and fall armyworm - Souza, Bruno H. S.; Costa, Eduardo N. [UNESP]; Ribeiro, Zulene A. [UNESP]; Perlatti, Bruno; Cruz, Mara C. P. [UNESP]; Forim, Moacir R.; Júnior, Arlindo L. Boiça [UNESP]; Stout, Michael J. (My University, 2021)
Numerous species of herbivorous insects are associated with soybeans, including the specialist velvetbean caterpillar (VBC), Anticarsia gemmatalis, and the generalist fall armyworm (FAW), Spodoptera frugiperda. Expression of plant resistance is influenced by factors intrinsic to host plants, such as leaf age and plant stage, which can differentially affect specialist and generalist insects due to varying levels of plant defense and corresponding insect adaptation. In this study, four experiments were carried out to test the hypotheses that levels of antibiosis-resistance to VBC and FAW in the resistant genotype PI 227,687 and susceptible genotype IGRA RA 626 RR are related to leaf age and plant stage of soybean. Furthermore, the concentrations of nutrients and selected flavonoids were quantified to give insights into possible chemical mechanisms underlying the resistance. As results, development of VBC and FAW were negatively affected when larvae fed leaves of the resistant genotype, older leaves from the lower part of plants, or leaves from reproductive-stage soybeans. The effects were partly different for each insect species, and the generalist FAW was more affected by higher resistance levels in the older leaves of soybean than the specialist VBC. Distribution and concentrations of nutrients and flavonoids in soybean in function of leaf age and plant stage may explain the varying levels of antibiosis-resistance to VBC and FAW. These results can benefit developments of specific protocols for screening resistant soybean genotypes and pest management strategies focused in plant parts and growth stages that insect-resistance levels are lowest.
Keywords: Flavonoids; Host plant resistance; Nutrients; Optimal defense theory; Plant–insect interaction